AIDA 0493 protocol for newly diagnosed acute promyelocytic leukemia: very long-term results and role of maintenance - Avvisati, Giuseppe; Lo-Coco, Francesco; Paoloni, Francesca Paola; Petti, Maria Concetta; Diverio, Daniela; Vignetti, Marco; Latagliata, Roberto; Specchia, Giorgina; Baccarani, Michele; Di Bona, Eros; Fioritoni, Giuseppe; Marmont, Filippo; et al. (Blood, 2011)
All-trans-retinoic acid (ATRA) has greatly modified the prognosis of acute promyelocytic leukemia; however, the role of maintenance in patients in molecular complete remission after consolidation treatment is still debated. From July 1993 to May 2000, 807 genetically proven newly diagnosed acute promyelocytic leukemia patients received ATRA plus idarubicin as induction, followed by 3 intensive consolidation courses. Thereafter, patients reverse-transcribed polymerase chain reaction–negative for the PML-RARA fusion gene were randomized into 4 arms: oral 6-mercaptopurine and intramuscular methotrexate (arm 1); ATRA alone (arm 2); 3 months of arm1 alternating to 15 days of arm 2 (arm 3); and no further therapy (arm 4). Starting from February 1997, randomization was limited to ATRA-containing arms only (arms 2 and 3). Complete remission was achieved in 761 of 807 (94.3%) patients, and 681 completed the consolidation program. Of these, 664 (97.5%) were evaluated for the PML-RARA fusion gene, and 586 of 646 (90.7%) who tested reverse-transcribed polymerase chain reaction–negative were randomized to maintenance. The event-free survival estimate at 12 years was 68.9% (95% confidence interval, 66.4%-71.4%), and no differences in disease-free survival at 12 years were observed among the maintenance arms.